2006
DOI: 10.1103/physrevd.74.059901
|View full text |Cite
|
Sign up to set email alerts
|

Publisher’s Note: Model-independent measurement ofS-waveKπ+systems usingD+→<

Abstract: A model-independent partial-wave analysis of the S-wave component of the Kπ system from decays of D + mesons to the three-body K − π + π + final state is described. Data come from the Fermilab E791 experiment. Amplitude measurements are made independently for ranges of K − π + invariant mass, and results are obtained below 825 MeV/c 2 , where previous measurements exist only in two mass bins. This method of parametrizing a three-body decay amplitude represents a new approach to analysing such decays. Though no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 15 publications
4
73
0
Order By: Relevance
“…[32,33] for analyses of similar B-meson decays), using various approximations in the description of final-state interactions. This corresponds to the rather good data situation for that channel [34][35][36][37]. However, a consistent, combined investigation of both final states is highly desirable, as they are coupled to each other by simple charge-exchange rescattering, but only the partially neutral final state allows for the observation of resonances in the pion-pion system (essentially the ρ(770)), while the π + π + system is necessarily a nonresonant isospin I = 2 state.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…[32,33] for analyses of similar B-meson decays), using various approximations in the description of final-state interactions. This corresponds to the rather good data situation for that channel [34][35][36][37]. However, a consistent, combined investigation of both final states is highly desirable, as they are coupled to each other by simple charge-exchange rescattering, but only the partially neutral final state allows for the observation of resonances in the pion-pion system (essentially the ρ(770)), while the π + π + system is necessarily a nonresonant isospin I = 2 state.…”
Section: Introductionsupporting
confidence: 65%
“…[26] concerning the phase motion of the I = 1/2 πK S -wave, whose phase rises much more quickly than the elastic scattering phase shift [56]. This has been observed before [34,37], but does not contradict Watson's final-state theorem [57]: the phase is modified due to rescattering with the third particle in the final state.…”
Section: Alternative D-wave Modelmentioning
confidence: 99%
“…To avoid the necessity for this model input in the freed-isobar approach, the dynamic amplitudes are replaced by sets of step-like functions, that approximate the dynamic amplitude by a set of constants α b within narrow bins b of m 2π [2]:…”
Section: Freed-isobar Partial Wave Analysismentioning
confidence: 99%
“…In order to study possible bias due to these parametrizations and to ensure that the observed a 1 (1420) signal is truly related to the narrow f 0 (980), a novel analysis method inspired by Ref. [19] was developed [4]. In this so-called freed-isobar analysis, the three fixed parametrizations for the 0 ++ isobar amplitudes are replaced by a set of piecewise constant complex-valued functions that fully cover the allowed two-pion mass range.…”
Section: Extraction Of ππ S-wave Isobar Amplitudes From Datamentioning
confidence: 99%